Biografický slovník - Slovenská akadémia vied - Historický Ústav (2014)
The General Database of the Biographical Dictionary of the Czech Lands has been compiled since 1990 to serve as the basis for the publication of a universal bibliographical dictionary. The dictionary’s aim is to provide essential information, verified by competent scholars, on the lives, activities and works of important Bohemian, Moravian and Silesian personalities throughout recorded history, especially in the domains of politics and policy, society, economics, technology, science and culture.